2015
DOI: 10.1007/s00296-015-3245-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in Egyptian patients with juvenile-onset systemic lupus erythematosus

Abstract: There are scanty data on the prevalence of vitamin D deficiency and its relation to disease activity among patients with juvenile-onset systemic lupus erythematosus (JoSLE) in the Middle East and North Africa, an area known to be endemic for vitamin D deficiency and insufficiency. The aim of this study was, therefore, to study vitamin D status and its relation to disease activity and parameters in Egyptian patients with JoSLE. Serum levels of 25(OH) D3 in 70 JoSLE patients were compared to 40 age-, sex-, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Thereafter, a number of larger-scale case-control studies confirmed the relationship between hypovitaminosis D and the prevalence of SLE [75,76,77,78], particularly in patients with lupus nephritis [75]. In our recent age- and gender-matched case-control study of 61 SLE patients and 61 healthy controls, we found that a deficiency of the total 25(OH)D 3 level, as measured by liquid chromatography-tandem mass spectrometry, was significantly more prevalent in the patient group (19.7% vs. 3.3%, p = 0.003) [79].…”
Section: Hypovitaminosis D and Its Impact On Disease Activity And mentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, a number of larger-scale case-control studies confirmed the relationship between hypovitaminosis D and the prevalence of SLE [75,76,77,78], particularly in patients with lupus nephritis [75]. In our recent age- and gender-matched case-control study of 61 SLE patients and 61 healthy controls, we found that a deficiency of the total 25(OH)D 3 level, as measured by liquid chromatography-tandem mass spectrometry, was significantly more prevalent in the patient group (19.7% vs. 3.3%, p = 0.003) [79].…”
Section: Hypovitaminosis D and Its Impact On Disease Activity And mentioning
confidence: 99%
“…In our recent age- and gender-matched case-control study of 61 SLE patients and 61 healthy controls, we found that a deficiency of the total 25(OH)D 3 level, as measured by liquid chromatography-tandem mass spectrometry, was significantly more prevalent in the patient group (19.7% vs. 3.3%, p = 0.003) [79]. Recently, a meta-analysis of 18 studies consisting of 1083 patients with SLE and 1273 healthy controls showed that the SLE patients had a significantly lower level of vitamin D compared with the healthy controls [76]. In addition, vitamin D deficiency was significantly more prevalent in the SLE patients when compared with the healthy controls, with a relative risk of 2.3 ( p = 0.002) [80].…”
Section: Hypovitaminosis D and Its Impact On Disease Activity And mentioning
confidence: 99%
“…251 Thieves' slang eloquently captures the artful connotations of crime: risovat', or to draw, means to kill; pero, or quill pen, is a knife. 252 The craft of pickpocketing, which a criminal in RUR described as the most "clever" of all types of theft, 253 at times required some unusual techniques. The prisoner Praskov'ia Skachko writes in her autobiography about the skill of stealing in church, an art form her husband taught her:…”
Section: The Art Of Crimementioning
confidence: 99%
“…This will be extremely embarrassing and will leave a bad impression in Japan." 41 In the same letter, written in February 1933, Shneiderov complains that, despite his promise to Tokyo Asahi to send five copies of his film within three months of his departure, the developed film footage had not even been printed a month later.…”
Section: The Impossibility Of "Talkie Realism"mentioning
confidence: 99%